Use of multidetector computed tomography angiography of upper limb circulation in patients undergoing coronary artery bypass grafting surgery - Altinsoy, Hasan B; Alatas, Ozkan; Kayancicek, Hidayet; Hafiz, Erhan; Dogan, Omer F (Indian Journal of Radiology and Imaging, 2017)
Objective: This study aimed to evaluate the bilateral forehand circulation using a 64-channel multidetector computed tomography (MDCT) as a noninvasive method to define criteria for an upper extremity arterial anatomy and pathology prior to the use of arterial conduits. Materials and Methods: Fifty-five patients with coronary artery disease who underwent total arterial coronary artery bypass grafting (CABG) were randomly selected for this prospective study. MDCT angiography was performed for 110 examinations of forearm and hand arterial anatomy. Prior to MDCT, Allen tests were performed in all patients with a normal result, except four. Thirteen patients had diabetes mellitus (DM), 8 had peripheral artery occlusive disease, and 19 had a history of smoking. Results: All arteries, including axillary, ulnar artery (UA) and radial artery (RA), were clearly visualized in all patients. Upper extremity anatomical and pathological results were examined in 16 patients (29.1%). Severely calcified RA and/or UA were found in 6 patients who had a moderate renal failure. Nearly total occlusion of the RA was detected in another two patients. Focal intimal RA calcification was recorded in 1 female and 3 male patients. Ten patients who had severe calcification or intimal sclerosis of the upper extremity arteries had DM. The remaining patients had normal forehand arterial circulation. A persistent median artery with the absence of radial and ulnar arteries and a high bifurcation of RA from the brachial artery was detected as an anatomic variation in seven patients (12.7%). Conclusions: The major advantages of MDCT angiography are its non-invasiveness and the ability to detect calcific subadventitial plaques, which are difficult to diagnose using conventional angiography. MDCT may be used as a safe and non-invasive method to assess RA and UA prior to harvesting the upper limb artery. Preoperative imaging of forehand arteries is a means to avoid unnecessary forearm exploration or the use of an unsuitable arterial conduit in CABG operations, especially in patients with DM and moderate renal impairment.
Keywords: Duplex ultrasonography; hand circulation; multislice computed tomography angiography